Titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin as well as preparation method and application of titanium-magnesium bimetallic catalyst

The etherification side reaction is inhibited by the titanium-magnesium bimetallic catalyst, and the problem of etherification side reaction during polyethylene naphthalate is solved, and the color and mechanical properties of the product are improved, which is suitable for high-end industrial applications.

CN119192551AActive Publication Date: 2024-12-27XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411478261.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

During the polyethylene naphthalate (PEN) polycondensation process, titanium catalysts are prone to etherification side reactions under high temperature conditions, resulting in oxidation and yellowing of the product, affecting the mechanical properties and optical transparency of the product. It is difficult for existing methods to obtain the following conditions Resolve this problem at the root.

Method used

The titanium-magnesium bimetallic catalyst is used to form a multi-compartmented ring intermediate with ester bonds and hydroxyl groups, adjust the electron cloud arrangement within the molecule, inhibit the occurrence of etherification side reactions, and reduce the formation of diethylene glycol fragments.

Benefits of technology

It effectively avoids the yellowing problem of PEN resin, significantly improves the color and quality of the product, reduces the amount of catalyst, improves the regularity and strength of the product, and is suitable for industrial applications that require excellent physical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192551A_ABST
    Figure CN119192551A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin and a preparation method and application thereof, and the preparation method comprises the following steps: carrying out static reaction on a titanium salt, a magnesium salt, a hydrolysis accelerant and water at 100-300 DEG C for 12-48 hours to obtain bimetallic gel; and adding ethylene glycol into the bimetallic gel, reacting at 80-180 DEG C for 3-6 hours, filtering, and drying to obtain the titanium-magnesium bimetallic catalyst for polymerization. According to the present invention, the titanium-magnesium bimetallic catalyst forms the polycyclic intermediate with the ester bond and the hydroxyl group, and the electron cloud arrangement mode is changed, such that the etherification side reaction is effectively inhibited, the generation of the diethylene glycol fragment is reduced, and the yellowing problem of the PEN resin is avoided. The catalyst has the advantages of simplicity in synthesis, remarkable catalytic effect, low chroma of PEN products and the like, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical industry, and specifically relates to a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin, and a preparation method and application thereof. Background Art

[0002] Polyethylene naphthalate (PEN) is a high-performance polyester material with excellent physical and chemical properties. In industry, it is often synthesized by polycondensation reaction of dimethyl naphthalate and ethylene glycol. The chemical structure of polyethylene naphthalate (PEN) is similar to that of polyethylene terephthalate (PET). The difference is that PEN replaces the benzene ring in the PET molecular chain with a more rigid naphthalene ring. The naphthalene ring structure makes PEN have higher performance than PET. Compared with PET resin, PEN resin has excellent thermal stability, small molecule barrier properties, UV barrier properties and chemical resistance. It is widely used in electronic information, high-end electronic device packaging, optical devices, special fibers and fabrics, and food packaging. It is known as one of the most influential emerging polymer materials in the 21st century.

[0003] Catalysts play a vital role in the polycondensation process of PEN. An ideal catalyst not only needs to efficiently promote the polycondensation reaction of PEN, increase the polymerization rate and the molecular weight of the product, but also must have excellent anti-side reaction ability under high temperature conditions, especially be able to inhibit the occurrence of etherification reactions. At present, the catalysts commonly used in industrial polyester synthesis are antimony-based, titanium-based, bismuth-based and zinc-based catalysts. For example, CN103772673A discloses a method for synthesizing PET polyester chips using titanium glycol as a catalyst, and a PET polyester product with a lower color value is obtained. CN118063746A discloses a polymerization catalyst containing antimony triacetate, which obtains a good catalytic effect. CN110577631A discloses a method for industrial synthesis of PEN using a titanium-based catalyst, and a high-viscosity PEN resin is obtained after solid-phase viscosity enhancement.

[0004] Among various catalysts, titanium-based catalysts have become one of the most widely used catalyst systems due to their high catalytic efficiency and low toxicity. However, under high temperature conditions during the polycondensation process, titanium-based catalysts are prone to induce etherification side reactions between hydroxyl groups in the polymerization reaction, which will generate excessive diethylene glycol fragments, further leading to increased oxidation and yellowing of polyester products, ultimately affecting the mechanical properties and optical transparency of the products. At present, the industry often avoids etherification side reactions by controlling the polymerization process, such as lowering the reaction temperature, adding antioxidants, etc. Although these methods have achieved certain results, they cannot solve the problem from the root.

[0005] Therefore, the selection of suitable catalysts, especially those that can maintain stability at high temperatures and inhibit etherification side reactions, is a key issue in the industrial production of PEN. Current research focuses on developing catalytic systems that can effectively control the reaction path and avoid etherification side reactions at high temperatures to ensure high-quality PEN products. Summary of the invention

[0006] In view of the problem that the etherification side reaction of PEN polycondensation reaction is uncontrollable under the titanium-based catalyst system in the prior art, the purpose of the present invention is to provide a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin and its preparation method and application. The catalyst interacts with the ester bond and hydroxyl group in the polyethylene naphthalate resin to form a polycyclic intermediate and adjusts the electron cloud arrangement inside the molecule, thereby successfully inhibiting the occurrence of the etherification side reaction. This mechanism effectively reduces the generation of diethylene glycol fragments, thereby avoiding the yellowing problem of PEN resin during the polymerization process, significantly improving the chromaticity and quality of the product, and has significant industrial application value.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin comprises the following steps: The titanium salt, the magnesium salt, the hydrolysis accelerator and water are subjected to a static reaction at 100-300° C. for 12-48 h to obtain a bimetallic gel; Ethylene glycol is added to the bimetallic gel and reacted at 80-180° C. for 3-6 hours, filtered, and dried to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0008] A further improvement of the present invention is that the molar ratio of the titanium salt, the magnesium salt and the hydrolysis accelerator is 0.5-1.5:1.0-3.0:0.005-0.02.

[0009] A further improvement of the present invention is that the mass of water is 2-4 times the total mass of the titanium salt, the magnesium salt and the hydrolysis promoter.

[0010] A further improvement of the present invention is that the titanium salt is tetrabutyl titanate or titanium chloride.

[0011] A further improvement of the present invention is that the magnesium salt is magnesium acetate, magnesium nitrate or magnesium chloride.

[0012] A further improvement of the present invention is that the hydrolysis accelerator is one of ammonia water, sodium bicarbonate, sodium acetate, methylamine, and pyridine, or a mixture of two of them.

[0013] A further improvement of the present invention is that when the hydrolysis accelerator is a mixture of two substances among ammonia water, sodium bicarbonate, sodium acetate, methylamine and pyridine, the mass ratio of the two substances is 1:1.

[0014] A further improvement of the present invention is that the mass of ethylene glycol is 1-3 times the mass of the bimetallic gel.

[0015] A titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin, wherein the catalyst has an intrinsic viscosity of 0.65-1.10 dL / g, a diethylene glycol content of 0.05%-1%, a yellowness value YI of 0.05-0.5, and a light transmittance of more than 89%.

[0016] The invention discloses an application of a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin in synthesizing PEN resin.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The catalyst production process is simple. The bimetallic catalyst provided by the present invention uses conventional chemical reagents, has relatively mild reaction conditions, uses less solvent, has a low calcination temperature, consumes less energy, has a short total preparation time, and has high feasibility for industrial production. It overcomes the problem of a complex preparation process in the existing industry, which is often synthesized through multiple steps such as high-temperature and high-pressure hydrolysis, multi-stage impregnation, ultrasonic washing and dispersion, high-temperature calcination, physical grinding and crushing, and screening.

[0018] (2) High catalytic efficiency. The amount of the bimetallic catalyst used in the present invention is significantly reduced. Only 0.3% of the total mass needs to be added to achieve the same polymerization effect and synthesize PEN products with the same grade of intrinsic viscosity. This overcomes the problem of adding about 0.5% of the total mass to synthesize polyester resins with a characteristic viscosity greater than 0.6 Dl / g in the existing industry. The high efficiency of this catalyst not only reduces the amount of catalyst used, saving production costs, but also reduces the incidence of side reactions in the production process, further improving product quality and consistency. In addition, reducing the amount of catalyst used can also reduce the potential impact of metal residues on product performance, meet the requirements of green and environmentally friendly production, and have great industrial application value.

[0019] (3) Fewer etherification side reactions. The titanium-magnesium bimetallic catalyst in the present invention forms a polycyclic intermediate with ester bonds and hydroxyl groups and changes the electron cloud arrangement, thereby effectively inhibiting the occurrence of etherification side reactions and reducing the generation of diethylene glycol fragments. It can effectively avoid the occurrence of etherification side reactions and avoid the yellowing problem of PEN resin. The content of the product is as low as 0.5% or less, the polymer molecular chain has good regularity and is easy to crystallize. It is easier to crystallize during the processing process to form a higher strength PEN product. The catalyst has the advantages of simple synthesis, significant catalytic effect, and low chromaticity of PEN products, and is suitable for industrial application scenarios requiring excellent physical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1This is the infrared spectrum of the titanium-magnesium bimetallic catalyst of Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention will be described more fully below in conjunction with the embodiments. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0022] Traditional titanium-based catalysts are often used in the preparation of PEN resins due to their high catalytic efficiency and low toxicity. However, under high temperature conditions, titanium-based catalysts easily induce hydroxyl etherification side reactions in polymerization reactions, generating excessive diethylene glycol fragments, which in turn lead to oxidation and yellowing of the product, affecting product quality. The titanium-magnesium bimetallic catalyst in the present invention forms polycyclic intermediates with ester bonds and hydroxyl groups and changes the electron cloud arrangement, thereby effectively inhibiting the occurrence of etherification side reactions, reducing the generation of diethylene glycol fragments, and avoiding the yellowing problem of PEN resin. The catalyst has the advantages of simple synthesis, significant catalytic effect, and low chromaticity of PEN products, and has broad prospects for industrial application.

[0023] The present invention provides a method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate (PEN) resin, the steps of which are as follows: Titanium salt (tetrabutyl titanate or titanium chloride), magnesium salt (magnesium acetate, magnesium nitrate or magnesium chloride) and hydrolysis accelerator are weighed into a high-pressure reactor according to a molar ratio of 0.5-1.5:1.0-3.0:0.005-0.02; water with a mass of 2-4 times the total mass of the above mixture is added; after stirring evenly, the temperature is raised to 100-300°C, and a static reaction is performed for 12-48 hours to obtain a bimetallic gel; ethylene glycol solvent is added to the system with a mass of 1-3 times the mass of the bimetallic gel, the temperature is raised to 80-180°C, and the reaction is stirred for 3-6 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension is placed in an oven at 100-220°C and dried for 2-3 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0024] The hydrolysis accelerator is one or a mixture of two of ammonia water, sodium bicarbonate, sodium acetate, methylamine and pyridine, and the mass ratio of the two substances is 1:1.

[0025] The performance evaluation of titanium-magnesium bimetallic catalyst was carried out by the following method: Weigh 153.0 g of dimethyl naphthalate, 97.0 g of ethylene glycol, and 0.75 g of a titanium-magnesium bimetallic catalyst in a stainless steel reactor, heat to 220°C and react for 2 h to carry out an ester exchange reaction, releasing by-product methanol from the system; continue to heat to 300°C, and reduce the pressure of the reaction system to 100 Pa. After reacting for 2 h under this condition, discharge the material while hot, and obtain PEN resin after pelletizing.

[0026] The PEN resin performance evaluation method is as follows: Intrinsic viscosity test: According to GB / T 14190-2008, dissolve an appropriate amount of PEN resin in a mixed solvent of phenol + tetrachloroethane (mass ratio = 1:1), use a syringe to fill the PEN solution into the Ubbelohde viscometer, ensure that there are no bubbles in the solution, record the time for the solution to stay from the upper mark line to the lower mark line, and record the outflow time of the solvent. Finally, use the viscosity formula to calculate the intrinsic viscosity of the PEN product.

[0027] DEG content test: Take appropriate amount of PEN resin and methanol and place them in a hydrothermal autoclave. After alcoholysis at 200℃ for 2 h, the degradation product is obtained. At the same time, methanol is used as solvent and ethylene glycol and diethylene glycol are used as solutes to prepare standard solutions of different concentrations for establishing a standard curve. Set appropriate parameters on the gas chromatograph (Pico, GC-6860 SA, HP-INNOWAX), record the retention time of the substance and the elution peak area, and calculate the DEG content.

[0028] The yellowness value YI was tested using a digital colorimeter (Sanshi, SHTI-101) in three parallel tests and the average value was recorded.

[0029] Light transmittance test: Cut the PEN film into a 100*100cm shape and test the light transmittance on a UV spectrophotometer.

[0030] The mass concentration of ammonia water in the present invention is 25%.

[0031] The technical solution of the present invention is described in detail below through specific embodiments: Example 1 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0032] See also Figure 1 , it can be seen that 1125 cm -1The absorption peak of Ti-O bond is 1438 cm -1 The absorption peak of Mg-O bond is 3450 cm -1 The peak at 2950 cm-1 is the stretching vibration peak of the hydroxyl group in the catalyst. -1 1718 is the stretching vibration peak of methyl group in the catalyst, and 1718 is the stretching vibration peak of ester bond in the catalyst. The above infrared spectra prove the successful preparation of bimetallic catalyst.

[0033] The performance evaluation operation steps of titanium-magnesium bimetallic catalyst are as follows: 153.0 g of dimethyl naphthalate, 97.0 g of ethylene glycol and 0.75 g of titanium-magnesium bimetallic catalyst are weighed in a stainless steel reactor, the temperature is raised to 220°C for 2 h to carry out ester exchange reaction, and the by-product methanol is released from the system; the temperature is continued to be raised to 300°C, and the pressure of the reaction system is reduced to 100 Pa. After reacting for 2 h under this condition, the material is discharged while hot and pelletized to obtain PEN resin.

[0034] Example 2 33.6 g of tetrabutyl titanate, 16.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0035] The catalyst performance evaluation procedure is the same as that in Example 1.

[0036] Example 3 27.6 g of tetrabutyl titanate, 22.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0037] The catalyst performance evaluation procedure is the same as that in Example 1.

[0038] Example 4 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.005 g of ammonia water, 0.005 g of sodium bicarbonate and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, and the temperature was raised to 120°C and stirred for reaction for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0039] The catalyst performance evaluation procedure is the same as that in Example 1.

[0040] Example 5 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.005 g of ammonia water, 0.005 g of pyridine and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, and the temperature was raised to 120°C and stirred for reaction for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0041] The catalyst performance evaluation procedure is the same as that in Example 1.

[0042] Example 6 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.02 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0043] The catalyst performance evaluation procedure is the same as that in Example 1.

[0044] Example 7 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 100 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0045] The catalyst performance evaluation procedure is the same as that in Example 1.

[0046] Example 8 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 260°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0047] The catalyst performance evaluation procedure is the same as that in Example 1.

[0048] Example 9 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 36 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0049] The catalyst performance evaluation procedure is the same as that in Example 1.

[0050] Example 10 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 400 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0051] The catalyst performance evaluation procedure is the same as that in Example 1.

[0052] Embodiment 11 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 160°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0053] The catalyst performance evaluation procedure is the same as that in Example 1.

[0054] Example 12 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 6 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0055] The catalyst performance evaluation procedure is the same as that in Example 1.

[0056] Embodiment 13 Titanium chloride (30.6 g), magnesium acetate and sodium acetate were weighed into a high-pressure reactor in a molar ratio of 0.5:1.5:0.005; water with a mass twice that of the total mass of the above mixture was added; the mixture was stirred evenly and heated to 100°C, and statically reacted for 48 hours to obtain a bimetallic gel; ethylene glycol solvent was added to the system with a mass three times that of the bimetallic gel, and the mixture was heated to 100°C and stirred for reaction for 5 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in an oven at 150°C and dried for 25 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0057] Embodiment 14 Tetrabutyl titanate, magnesium nitrate and methylamine were weighed into a high-pressure reactor in a molar ratio of 1.0:1.01:0.02; water with a mass 4 times the total mass of the above mixture was added; the mixture was stirred evenly and heated to 300°C, and statically reacted for 12 hours to obtain a bimetallic gel; ethylene glycol solvent was added to the system with a mass twice that of the bimetallic gel, and the mixture was heated to 180°C and stirred for reaction for 3 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in an oven at 220°C and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0058] Embodiment 15 Tetrabutyl titanate, magnesium chloride and pyridine were weighed into a high-pressure reactor in a molar ratio of 1.5:3.0:0.01; water with a mass three times the total mass of the above mixture was added; after stirring evenly, the temperature was raised to 150°C, and a static reaction was performed for 30 hours to obtain a bimetallic gel; ethylene glycol solvent was added to the system with a mass of 1 times the mass of the bimetallic gel, and the temperature was raised to 80°C and stirred for reaction for 6 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in an oven at 100°C and dried for 3 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0059] Comparative Example 1 40.0 g of tetrabutyl titanate, 10.0 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0060] The catalyst performance evaluation procedure is the same as that in Example 1.

[0061] Comparative Example 2 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0062] The catalyst performance evaluation procedure is the same as that in Example 1.

[0063] Comparative Example 3 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 220 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0064] The catalyst performance evaluation procedure is the same as that in Example 1.

[0065] Comparative Example 4 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 80°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained by filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0066] The catalyst performance evaluation procedure is the same as that in Example 1.

[0067] Comparative Example 5 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 60 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0068] The catalyst performance evaluation procedure is the same as that in Example 1.

[0069] Comparative Example 6 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 700 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0070] The catalyst performance evaluation procedure is the same as that in Example 1.

[0071] Comparative Example 7 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a bimetallic gel was obtained after static reaction for 24 hours; 200 g of ethylene glycol was added to the system, and the temperature was raised to 200°C and stirred for reaction for 4 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0072] The catalyst performance evaluation procedure is the same as that in Example 1.

[0073] Comparative Example 8 30.6 g of tetrabutyl titanate, 19.4 g of magnesium acetate, 0.01 g of ammonia water and 150 g of water were put into a high-pressure reactor; after stirring evenly, the temperature was raised to 200°C, and a static reaction was performed for 24 hours to obtain a bimetallic gel; 200 g of ethylene glycol was added to the system, the temperature was raised to 120°C, and the reaction was stirred for 2 hours to obtain a bimetallic catalyst suspension; the filter cake obtained after filtering the above suspension was placed in a 200°C oven and dried for 2 hours to obtain a titanium-magnesium bimetallic catalyst for polymerization.

[0074] The catalyst performance evaluation procedure is the same as that in Example 1.

[0075] The preparation conditions of Examples 1-12 and Comparative Examples 1-8 are shown in Table 1, and the performance comparison is shown in Table 2.

[0076] Table 1 Synthesis data of examples and comparative examples

[0077] Table 2 Comparison of the properties of PEN resins obtained in Examples and Comparative Examples

[0078] According to Examples 1-13 and Comparative Examples 1-8, it can be seen that in Comparative Example 1, the ratio of the titanium source and the magnesium source exceeds the range of the dosage ratio in the present invention, the ratio of the metal atoms in the catalyst obtained is changed, it is difficult to form a polycyclic intermediate with the active group of the polymer, the catalytic performance is poor, and a PEN polymer with a high intrinsic viscosity cannot be obtained; in Comparative Example 2, the amount of the hydrolysis promoter is too much, resulting in the formation of inert metal oxides, which cannot show good catalytic performance; in Comparative Example 3, the amount of water is too much, exceeding the scope of the claims, resulting in a decrease in the unit volume concentration of metal atoms, and it is impossible to effectively catalyze PEN polymerization; in Comparative Example 4, the static reaction temperature is too low , the catalyst substrate cannot react completely, resulting in an imperfect catalyst structure and inability to effectively catalyze the polymerization reaction; in comparative example 5, the static reaction time is too long, exceeding the reaction time range of the present invention, so that inert metal oxides are formed in the system, which leads to poor catalytic performance; in comparative example 6, the amount of ethylene glycol is too much, which destroys the structure of the bimetallic gel, resulting in reduced catalyst performance; in comparative example 7, the stirring reaction temperature is too high, resulting in the formation of the gel structure at high temperature. The catalytic effect of the catalyst is reduced; in comparative example 8, the stirring reaction time is too short, and the catalyst microstructure has not been fully formed, resulting in reduced catalytic efficiency. The present invention can solve the problem of yellowing of the product caused by the etherification side reaction induced by the traditional titanium-based catalyst. The PEN resin synthesized with titanium-magnesium bimetallic catalyst has excellent performance, an intrinsic viscosity of 0.45-1.10 dL / g, a diethylene glycol content of 0.05%-1%, a yellowness value YI of 0.05-0.50, and a light transmittance of 89%-93%, and has broad industrial application prospects and commercial value.

[0079] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin, characterized in that: The following steps are involved: The titanium salt, the magnesium salt, the hydrolysis accelerator and water are subjected to a static reaction at 100-300° C. for 12-48 h to obtain a bimetallic gel; Ethylene glycol is added to the bimetallic gel and reacted at 80-180° C. for 3-6 hours, filtered, and dried to obtain a titanium-magnesium bimetallic catalyst for polymerization.

2. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The molar ratio of titanium salt, magnesium salt and hydrolysis accelerator is 0.5-1.5:1.0-3.0:0.005-0.

02.

3. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The mass of water is 2-4 times the total mass of the titanium salt, magnesium salt and hydrolysis accelerator.

4. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The titanium salt is tetrabutyl titanate or titanium chloride.

5. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The magnesium salt is magnesium acetate, magnesium nitrate or magnesium chloride.

6. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The hydrolysis accelerator is one of ammonia water, sodium bicarbonate, sodium acetate, methylamine and pyridine, or a mixture of two of them.

7. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 6, characterized in that: When the hydrolysis accelerator is a mixture of two substances among ammonia water, sodium bicarbonate, sodium acetate, methylamine and pyridine, the mass ratio of the two substances is 1:

1.

8. The method for preparing a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin according to claim 1, characterized in that: The mass of ethylene glycol is 1-3 times the mass of the bimetallic gel.

9. A titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin prepared according to the method according to any one of claims 1 to 8, characterized in that: The catalyst has an intrinsic viscosity of 0.65-1.10 dL / g, a diethylene glycol content of 0.05%-1%, a yellowness value YI of 0.05-0.5, and a light transmittance of more than 89%.

10. Use of a titanium-magnesium bimetallic catalyst for synthesizing polyethylene naphthalate resin prepared by the method according to any one of claims 1 to 8 in synthesizing PEN resin.

Citation Information

Patent Citations

  • Preparation method of low-temperature sintering nano-sized magnesium titanate powder

    CN102030364A

  • Preparation method and application of hydrolysis-resistant high-activity bimetallic titanium catalyst

    CN118325048A

  • Ti-Mg bimetallic titanium catalyst as well as preparation method and application thereof

    CN118667136A

  • Manufacture of polybutylene naphthalate

    JP2000159877A

Cited By

  • Polyester fiber suitable for non-aqueous medium dyeing and preparation method thereof

    CN121023674A